Service-oriented computing in manufacturing automation: a SWOT analysis - Mendes, João M. (2011)
Service-oriented Computing (SOC) is being applied in industrial manufacturing automation to face the current demand for modular, flexible and reconfigurable solutions. Highlighted from the other existing methodologies, SOC may carry an alternative but natural solution to design and engineer manufacturing automation systems and consequently the ability to seamless integrate into the modern IT-enterprise. However, SOC still has a long way to be adopted by industrial solutions, mainly fulfilling the particularities of the manufacturing domain. This paper discusses the applicability of the SOC in industrial manufacturing automation by using a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. The discussed aspects show the great potential of SOC to solve industrial manufacturing automation problems, but also the